The relationship between insecurity and the quality of hospital care provided to women with abortion‐related complications in the Democratic Republic of Congo: A cross‐sectional analysis. (10th December 2021) - Wolomby‐Molondo, Jean‐José; Calvert, Clara; Seguin, Rachelle; Qureshi, Zahida; Tunçalp, Özge; Filippi, Véronique
Abstract: Objective: To examine the relationship between insecurity and quality of care provided for abortion complications in high‐volume hospitals in the Democratic Republic of Congo (DRC). Methods: Using the WHO Multi‐Country Survey on Abortion complications, we analyzed data for 1007 women who received care in 24 facilities in DRC. For inputs of care, we calculated the percentage of facilities in secure and insecure areas meeting 12 readiness criteria for infrastructure and capability. For process and outcomes of care, we estimated the association between security and eight indicators using generalized estimating equation models. Results: Facilities in secure areas were more likely to report functioning electricity (93.3% vs 66.7%), availability of an obstetrician 24/7 (42.9% vs 28.6%), and the ability to offer several short‐acting contraceptives (83.3% vs 57.1%). However, a higher percentage of facilities in insecure areas reported the availability of a telephone or radio (100% vs 80.0%). Women in insecure areas appeared more likely to experience poor quality clinical care overall than women in secure areas (aOR 2.56; 95% CI, 1.13–5.82, P  = 0.03). However, there was no association between security and incomplete medical records ( P  = 0.20), use of dilatation and curettage (D&C) ( P  = 0.84), women reporting poor experience of care ( P  = 0.22), satisfaction with care ( P  = 0.25), and severe maternal outcomes ( P  = 0.56). There was weak evidence of an association between security and nonreceipt of contraceptives ( P  = 0.07), with women in insecure areas 70% less likely to report no contraception (aOR 0.31, 95% CI, 0.09–1.09). Use of D&C was high in secure (43.7%) and insecure (60.4%) areas. Conclusion: Quality of care did not seem to be very different in secure and insecure areas in DRC, except for some key infrastructure, supply, and human resources elements. The frequent use of D&C for uterine evacuation, the lack of good record keeping, and the lack of contraceptives should be urgently addressed. Synopsis: Except for facility capability, the quality of care for abortion complications is similar in secure and insecure areas in the Democratic Republic of Congo, with frequent use of dilatation and curettage.